Проблемы реинжиниринга программных legacy-систем - Пашковец, Н.Д.; Бабак, О.В. (Інститут програмних систем НАН України, 2010)
В работе изложен подход к анализу программных систем с целью автоматизации разбора и отображения логики, лежащей в основе их функционирования. Главное внимание направлено на выделение бизнес-объектов и идентификации бизнес-терминов как элементарных составляющих, на которых базируется описание и построение логических схем и структур программных legacy-систем. Изложено обоснование предлагаемого подхода к реинжинирингу программных legacy-систем и определяются условия корректного построения комплекса бизнес-правил. Предложена методика и алгоритмы автоматизации определения паттернов в модулях legacy-систем, выделение которых позволяет решать проблемы обобщения, унификации и классификации создаваемых бизнес-правил в рамках конкретной legacy-системы или ряда legacy-систем, относящихся к одному типу, при проведении их реинжиниринга. Разработана общая технология построения БП в виде взаимосвязанных средств автоматизации построения БП (САПБП) для выполнения реинжиниринга программных legacy-систем. The article describes the approach to the analysis of software systems to automate the parsing and display logic that underlies their functioning. The main attention is directed to the provision of business objects and identification of business terms as the elementary constituents, which is based on the description and the construction of logic circuits and structures of software legacy-systems. Set out the rationale of the proposed approach to reengineering legacy-software systems and defines the conditions for constructing a correct set of business rules. The technique and algorithms for automation of certain patterns in the modules of legacy-systems, the allocation that solves the problems of consolidation, harmonization of classification and create business rules within a particular legacy-system or some legacy-systems belonging to the same type, during their re-engineering. A general technique for constructing BP in the form of interconnected building automation BP (SAPBP) for performing software reengineering legacy-systems.